Current advancements in pharmacotherapy for cancer cachexia. (24th March 2023) - da Fonseca, Guilherme Wesley Peixoto; Sato, Ryosuke; de Nazaré Nunes Alves, Maria Janieire; von Haehling, Stephan
ABSTRACT: Introduction: Cancer cachexia is a multifactorial metabolic syndrome associated with a pathophysiology intertwined with increased inflammatory response, anorexia, metabolic dysregulation, insulin resistance, and hormonal alterations, which together generate a negative energy balance in favor of catabolism. The development of therapeutic strategies to treat cancer cachexia has always been related to clinical interventions with increased food intake/supplementation, physical exercise regimens, and/or medication to attenuate catabolism and increase the anabolic response. However, the approval of drugs by regulatory agencies has always been a challenge. Areas covered: This review outlines the main pharmacotherapy findings in cancer cachexia as well as the ongoing clinical trials that have evaluated changes in body composition and muscle function. The National Library of Medicine (PubMed) was used as search tool. Expert opinion: The pharmacological therapy for cachexia should be focused on improving body composition, muscle function, and mortality, although none of the compounds used so far was able to demonstrate positive results beyond increased appetite and improvements in body composition. Ponsegromab (GDF15 inhibitor), a new compound that has just entered a phase II clinical trial, is a promising candidate to treat cancer cachexia and may produce exciting results if the study can be conducted as planned.